Multimedia in Foreign Language Learning - Dovedan Han, Zdravko; Seljan, Sanja; Kocijan, Kristina (2002)
Computer technology and Internet are inevitable new media in education methodology. Still, the central role in teaching belongs to humans. The power of Internet lies in offering authentic materials, software, education plans, list of exams, literature, etc. to schools, universities, and institutions all over the world but under the same conditions. Next to its commercial importance, it is seen as pedagogical tool for either the independent research or teamwork. The paper brings out positive and negative effects of new technology and its implementation in foreign language learning. Besides for the lessons learning, the idea of information literacy maintains crucial position in education. The new technology demands investment of time, effort, money, and self-education, so that the principal question remains: Are we ready for new type of education in order to offer better teaching, more interesting lessons and more importantly, to prepare new generations for future challenges?
Projekt MZOS
ENG